“O importante é ter na mesa”: análise da cadeia de comercialização do açaí oriundo de ilhas de Abaetetuba, Pará – dinâmicas, atores e formação de preço - SANTOS, Sávio Silva dos (2019)
This work presents a productive line of the açaí from the Quilombola Community Sacred Heart of Jesus - Rio Genipaúba - Abaetetuba Islands. We start from the hypothesis that açaí commercialized internally, in the different categories, presents particularities in the process of formation and price variation, which differs from most agricultural products, in the periods of harvest and off season, with Informal agreements to define price and quality of products. For this purpose, we used qualitative and quantitative approaches, considering that the methodological procedures involved bibliographic research and, also, field research, the occasion when the observation was performed and the questionnaire was applied Semi-structured to 17 (seventeen) interviewed workers, from October 23, 2018 to May 09, 2019, for further analysis and tabulation of data. As main results, it was possible to identify 4 (four) main actors of the commercialization chain: Producers, Marreteiros, Traversers and scouts, who exploit the income of açaí as the main economic source; Informal buying and selling agreements predominate; The price suffers a lot of variation in the crop and off season, but there is a local strategy of maintaining the price to the final consumer, altering the dilution of the product.